Metodyka ustalania kosztów jednostkowych leczenia pacjentów - Hass-Symotiuk, Maria (The overview of the cost calculation methods for inpatient treatment in hospital departments, 2008)
The article presents the principles of cost calculations of inpatient treatment in hospital departments and their structure. The article is focused on the requirements of cost calculations of medical procedures assigned to the individual patients, principles of unit cost calculations and their potential benefits.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 95-104